Fishes of the western North Atlantic. Polymixiidae, Berycidae, Diretmidae, Trachichthyidae, Anomalopidae, Holocentridae, Anoplogasteridae ; Order Xenoberyces (Stephanoberyciformes) : Gibberichthyidae, Stephanoberycidae, Melamphaidae ; Order Anacanthini (Gadiformes) in part Macrouridae /: Polymixiidae, Berycidae, Diretmidae, Trachichthyidae, Anomalopidae, Holocentridae, Anoplogasteridae ; Order Xenoberyces (Stephanoberyciformes) : Gibberichthyidae, Stephanoberycidae, Melamphaidae ; Order Anacanthini (Gadiformes) in part Macrouridae. Order Heteromi (Notacanthiformes), Halosauridae, Notacanthidae, Lipogenyidae ; Suborder Cyprinodontoidei ; Order Berycomorphi (Beryciformes) : Part Six, ([2018]) - Cohen, Daniel M
No abstract available